Pauropoda (Myriapoda) from Great Smoky Mountains National Park, U.S.A., with descriptions of four new species - Scheller, Ulf (Zootaxa, 2011)
As a part of the All-Taxa Biodiversity Inventory of Great Smoky Mountains National Park (Tennessee, North Carolina, U.S.A.) a collection of 192 specimens of Pauropoda has been studied. Eighteen species belonging to six genera in three families have been identified. Four of the species in Pauropodidae are new to science and described: Decapauropus arcuatilis n. sp., Stylopauropus plicatus n. sp., Donzelotauropus dividuus n. sp. and Donzelotauropus tenuitarsus n. sp. With the four new species the number of known species in GSMNP now stands at 49. A key is presented to the genera collected up to now in GSMNP.